Christian Reflections on the Relationship of Leisure and Work - Paul Heintzman (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2012)
A Christian understanding of leisure cannot be developed in isolation from the other dimensions of life. In the creation account of Genesis we learn that both rest and work are basic to the created nature of humanity. The purpose of this paper is to explore a Christian understanding of the relationship between leisure and work. The paper begins with a brief review of biblical teaching on work and leisure. This teaching is then applied to a critique of five more recent perceptions of the relationship of leisure and work: work-oriented unilateral; leisure-oriented unilateral; split; integrated; and identity. It is argued that the identity approach, which is consistent with a holistic understanding of leisure, is most congruent with a biblical understanding of leisure and work. Our work is to flow from a quality of life, a spiritual attitude characterized by rest in God. In addition, some rhythm or cycle of work and leisure (in a quantitative sense) is necessary for well-being and wholeness. Thus in addition to leisure as a spiritual attitude, certain times and activities—ranging from silent contemplation to an active celebration and rejoicing in the gifts of creation—are necessary when an intensification of leisure is experienced.
Keywords: Leisure; spirituality; recreation; work